Waqf Higher Education: Implementation Model In University College Bestari (UCB), Terengganu, Malaysia - Baharuddin Bin Sayin; Muhammad Hamizan Bin Ab Hamid (Media Syari'ah, 2020)
Waqf higher education was an important asset in developing knowledgeable intellectuals. This waqf higher education was a successful institution that uses waqf as it source of operation. It can be seen through the model of College University Bestari (UCB) in the implementation of higher education waqf. The objective of this writing is to focus on the historical background, the development of waqf asset, contribution and beneficial distribution of waqf property as well as challenges and prospects of higher education in Malaysia. The analysis result found that UCB had been successfully expanded the waqf funds through the waqf scheme of land lot by getting approval from Terengganu Islamic Religious and Malay Customs Council (MAIDAM). Thus, the implementation of educational waqf held by UCB can be used as a model to other educational institutions in order to develop waqf property and generate revenue. Therefore, the model that existed in this waqf institution need to be systematically planned and implemented to ensure that it can be a guarantee and catalyst towards education finance system of the Muslim community.